Nonequilibrium quantum thermodynamics in Coulomb crystals - Cosco F; Borrelli M; Silvi P; Maniscalco S; De Chiara G (AMER PHYSICAL SOC, 2022)
We present an in-depth study of the nonequilibrium statistics of the irreversible work produced during sudden quenches in proximity to the structural linear-zigzag transition of ion Coulomb crystals in 1+1 dimensions. By employing both an analytical approach based on a harmonic expansion and numerical simulations, we show the divergence of the average irreversible work in proximity to the transition. We show that the nonanalytic behavior of the work fluctuations can be characterized in terms of the critical exponents of the quantum Ising chain. Due to the technological advancements in trapped-ion experiments, our results can be readily verified.